Investigation on colour, fastness properties and HPLC-DAD analysis of silk fibres dyed with Rubia tinctorium L. and Quercus ithaburensis Decaisne - YILMAZ, BURCU (WILEY, 2012)
Silk fabric samples were dyed according to the various procedures using madder (Rubia tinctorium L.) and walloon oak (Quercus ithaburensis Decaisne) extracts. The colour coordinates, K/S, as well as wash, light, rub and perspiration fastness values were determined. A reversed-phase high-performance liquid chromatography with diode-array detection was utilised for the identification of the components of dyes present in the dyed fabrics and in the plant extracts.
Keywords: NATURAL RED DYES; TEXTILES; IDENTIFICATION; MADDER; EXTRACTION; PIGMENTS; ANTHRAQUINONES; ALIZARIN; MATTERS; LAKES